2022
DOI: 10.1007/s10880-022-09915-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Workplace Bullying with Suicide Ideation and Attempt Among Chinese Nurses During the COVID-19 Pandemic

Abstract: Nurses experience a high incidence of workplace bullying and are at a higher risk of suicide than the general population. However, there is no empirical evidence on how exposure to workplace bullying is associated with suicide ideation and attempts among nurses. Nurses were recruited from tertiary hospitals in Shandong Province, China, using stratified cluster sampling. Suicide ideation and attempts were assessed using two items, and the Workplace Psychologically Violent Behaviors Instrument was used to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In this study, we found that social isolation, one of the four subscales of morbidity stigma, was an independent risk factor for suicidality risk after excluding confounding factors, supporting earlier research. 37 Determining the risk of those who exhibit suicidal ideation, attempt suicide, or engage in self-harm activity requires taking into account one's experience of solitude; 38 3) Research has also shown that insight is a double-edged sword, although high insight can make patients aware of the symptoms of their illness, at the same time, it can make patients with schizophrenia feel stigmatized, 39,40 studies have shown that self-stigmatization mediates the relationship between insight and psychosocial outcomes in people with schizophrenia. Consequently, lowering self-stigma might aid in attenuating some of the negative effects of high insight on psychosocial outcomes in patients with schizophrenia, 40 In addition, we found a number of demographic characteristics in our study that were also associated with suicidality among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that social isolation, one of the four subscales of morbidity stigma, was an independent risk factor for suicidality risk after excluding confounding factors, supporting earlier research. 37 Determining the risk of those who exhibit suicidal ideation, attempt suicide, or engage in self-harm activity requires taking into account one's experience of solitude; 38 3) Research has also shown that insight is a double-edged sword, although high insight can make patients aware of the symptoms of their illness, at the same time, it can make patients with schizophrenia feel stigmatized, 39,40 studies have shown that self-stigmatization mediates the relationship between insight and psychosocial outcomes in people with schizophrenia. Consequently, lowering self-stigma might aid in attenuating some of the negative effects of high insight on psychosocial outcomes in patients with schizophrenia, 40 In addition, we found a number of demographic characteristics in our study that were also associated with suicidality among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The interpersonal theory of suicide (IPTS) suggests that workplace bullying can contribute to suicidal thoughts through two key factors: “thwarted belongingness” (feeling socially isolated) and “perceived burdensomeness” (believing one is a burden on others with little hope of improvement) 10 , 11 . Bullying has been reported to be associated with nurses’ suicidal ideation, suicidal attempts, and their suicide 12 . Numerous studies reported workplace bullying among nurses, which occurs primarily as a result of the authority's aggressive, violent, and frightening behavior or insulting behaviours by colleagues that make them feel irritated, humiliated, and threatened; thereby, their mental health is supposed to have deteriorated 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported workplace bullying among nurses, which occurs primarily as a result of the authority's aggressive, violent, and frightening behavior or insulting behaviours by colleagues that make them feel irritated, humiliated, and threatened; thereby, their mental health is supposed to have deteriorated 13 , 14 . According to a study, bullying among nurses is a fairly common occurrence that harms both nurses and patients 12 . It has been reported that the risk of patient death in clinical settings is significantly associated with bullying against nurses 15 .…”
Section: Introductionmentioning
confidence: 99%